THE INFLUENCE OF PROBLEM FINANCING ON THE PERFORMANCE OF SYARIAH BANKS IN INDONESIA - Lely Dwi Rahmawati; Haqiqi Rafsanjani; Tiara Anindya Virana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
In the context of economic globalization, the Islamic banking sector has demonstrated significant growth. However, a major challenge faced by Islamic banks is the high ratio of Non-Performing Financing (NPF), which can hinder the banks' financial performance. This study aims to investigate whether problematic financing, known as Non-Performing Financing (NPF), affects the financing performance of Islamic banks in Indonesia during the 2014-2023 period. The research adopts a quantitative approach using Time-Series methods and analytical techniques such as Vector Error Correction Model (VECM) to evaluate the relationship between Non-Performing Financing (NPF) and Return on Assets (ROA) and Capital Adequacy Ratio (CAR) as indicators of bank performance. The findings of this study reveal a negative relationship between NPF and both ROA and CAR, considering the importance of risk management in maintaining the performance of Islamic banks. This research contributes to understanding the performance dynamics of Islamic banks in Indonesia and their implications for financial system stability.